Synthetic hackmanites as detection materials for ionizing radiation - Vuori, Sami (My University, 2019)
Hackmanite (Na8Al6Si6O24(Cl,S)2) exhibits reversible photochromism or tenebrescence (Latin tenebra, shadow), which can be induced by exposure to UV light. In this phenomenon the off-white mineral turns pink or purple, and the original color can be restored with visible light or heat. For this to happen, there must be traps in the material’s crystal structure, and in hackmanite the traps are chloride vacancies which are sites where a chloride ion should reside, but due to sulfur anions being present, the charge balance does not allow a chloride ion to enter the structure at some point near the sulfur ion. The incident UV photon excites a sulfur atom’s electron which gets trapped in the vacancy. This creates an F center (German Farbzentrum, color center) which absorbs visible light in the green-yellow part (520−540 nm) of the spectrum, causing the coloration of the material. The aim of this study was to gain knowledge on how particle radiation and exposure to X-rays induce tenebrescence in hackmanites. The theoretical background reviews different types of radiation, current trends in radiation dosimetry and the use of thermoluminescence and optically stimulated luminescence in the ionizing radiation monitoring. Some theory about color spaces and representation models are discussed shortly. Finally, the X-ray analysis techniques used in the experimental section are reviewed. The experimental section focuses on the synthetically prepared hackmanite to gain knowledge on whether the material could be used as a novel application in the field of radiation detection and dosimetry. The section also contains specific instructions on how to make hackmanites and cast them as flexible tapes via the doctor blading method. Tiivistelmää muokattu työn hyväksymisen jälkeen 19.8.2019.
Keywords: chemistry,tenebrescence,photochromism,X-ray,tape casting,hackmanite,kemia,tenebresenssi,fotokromismi,röntgen,hackmaniitti